Characterization of Essential Oil Composition in Different Basil Species and Pot Cultures by a GC-MS Method - Muráriková, Andrea; Ťažký, Anton; Neugebauerová, Jarmila; Planková, Alexandra; Jampílek, Josef; Mučaji, Pavel; Mikuš, Peter (Molecules (Basel, Switzerland), 2017)
Basil (Ocimum L.) species are used as medicinal plants due to their essential oils exhibiting specific biological activity. The present work demonstrated that both the variety and season/conditions of cultivation had a significant effect on (i) the produced amount (extraction yield), (ii) qualitative, as well as (iii) quantitative profile of basil essential oil. Among studied basil varieties, a new variety, 'Mánes', was characterized for the first time. Based on our quantitative evaluation of GC-MS profiles, the following chemotypes and average concentrations of a main component were detected in the studied basil varieties: 'Ohře', 'Lettuce Leaf', 'Purple Opaal', 'Dark Green' (linalool, 5.99, 2.49, 2.34, 2.01 mg/mL, respectively), and 'Mammolo Genovese', 'Mánes', 'Red Rubin' (eucalyptol, 1.34, 0.96, 0.76 mg/mL, respectively). At the same time, when considering other compounds identified in GC-MS profiles, all the studied varieties, except from 'Lettuce Leaf', were methyl eugenol-rich with a strong dependence of the eugenol:methyl eugenol ratio on the seasonal changes (mainly solar irradiation, but also temperature and relative humidity). More complex and/or variable (depending on the season and cultivation) chemotypes were observed with 'Lettuce Leaf' (plus estragole, 2.27 mg/mL), 'Dark Green' (plus eucalyptol, 1.36 mg/mL), 'Mammolo Genovese' (plus eugenol, 1.19 mg/mL), 'Red Rubin' (plus linalool and eugenol, 0.46 and 0.56 mg/mL, respectively), and 'Mánes' (plus linalool and eugenol, 0.58 and 0.40 mg/mL, respectively). When considering superior extraction yield (ca. 17 mL·kg-1, i.e., two to five times higher than other examined varieties) and consistent amounts (yields) of essential oil when comparing inter-seasonal or inter-year data (RSD and inter-year difference in mean yield values ˂2.5%), this new basil variety is very promising for use in the pharmaceutical, food, and cosmetic industries.
Keywords: Eucalyptol; Plant Leaves; Monoterpenes; profiling; acyklické monoterpeny; eukalyptol; Anisoles; essential oils; oleje prchavé; Plant Oils; Cyclohexanols; Acyclic Monoterpenes; pot cultures; bazalka pravá; monoterpeny; listy rostlin; oleje rostlin; eugenol; bazalka; plynová chromatografie s hmotnostně spektrometrickou detekcí; basil varieties; cyklohexanoly; GC-MS analysis; Oils, Volatile; Ocimum; allylbenzenové deriváty; Allylbenzene Derivatives; Gas Chromatography-Mass Spectrometry; anisoly; Eugenol; Ocimum basilicum